2005
DOI: 10.1002/app.21727
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of paper strength with starch modified clay

Abstract: ABSTRACT:In order to improve the strength properties of high filler filled papers, a new technique of coating starch on the clay surface was developed. The stability of the coated starch and its effects on paper properties were studied. It was found that the starch coated on the clay surface swelled in water. This swelled starch film on the filler surface contributes significantly to the filler-filler bonding. The strength properties of handsheets made from starch coated clay, even with unmodified corn starch,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 1 publication
0
52
0
Order By: Relevance
“…Chauhan and Bhardwaj (2014) pre-flocculated talc with cationic starch, resulting in a 7% to 15% increase in tensile index with 24% filler content. Yan et al (2005) showed a significant improvement in the strength of paper filled with starch-coated clay compared with that filled with unmodified clay.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Chauhan and Bhardwaj (2014) pre-flocculated talc with cationic starch, resulting in a 7% to 15% increase in tensile index with 24% filler content. Yan et al (2005) showed a significant improvement in the strength of paper filled with starch-coated clay compared with that filled with unmodified clay.…”
Section: Introductionmentioning
confidence: 93%
“…However, paper strength can be negatively affected because the filler impedes the inter-fiber hydrogen bonding. To improve the strength of filled paper, many methods have been tried, such as strength additives (Hamzeha et al 2013), lumen loading (Miller and Paliwal 1985), filler pre-flocculation (Sang et al 2012;Chauhan and Bhardwaj 2014), and filler modification (Yan et al 2005;Zhao et al 2005;Yoon and Deng 2007;Shen et al 2009Shen et al , 2010. Among those methods, filler pre-flocculation and modification are of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Starch is currently the most widely used dry-strength agent because of its relatively low price and high performance. Starch has an abundance of hydroxyl groups, which form hydrogen bonds with wood fibers to improve paper strength (Marton 1996;Yan et al 2005). In practical applications, starches are often modified with a cationic charge or with amphoteric starches to increase starch retention.…”
Section: Introductionmentioning
confidence: 99%
“…Many approaches have been used in an attempt to solve the problems caused by filler addition, including modifications of milling (Christidis et al 2004), preflocculation (Ono and Deng 1997;Mabee et al 2000), synthesis of filler with different structures and functions (Enomae and Tsujino 2004), surface medication (Yan et al 2005;Zhao et al 2005;Yoon et al 2006;Deng et al 2008), lumen loading (Zakaria et al 2004;Yoon et al 2007), and using composite filler. In the current study, the use of mineral filler modified via polysaccharides and their derivatives is used as a valid approach to handle the problems associated with fillers (Yan et al 2005;Zhao et al 2005;Yoon and Deng 2006;Deng et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the use of mineral filler modified via polysaccharides and their derivatives is used as a valid approach to handle the problems associated with fillers (Yan et al 2005;Zhao et al 2005;Yoon and Deng 2006;Deng et al 2008). It is known that the use of starch gel coating has the benefits of maintaining paper strength and increasing filler loading.…”
Section: Introductionmentioning
confidence: 99%